RF speech processor / Jamaluddin Akhir Abdul Raof and Ibrahim Abdul Rahman - Abdul Raof, Jamaluddin Akhir; Abdul Rahman, Ibrahim (1989)
Spoken voice links are one of the least efficient ways of communicating information electrically, but the most natural to us humans. The classic compromise is to clip or to compress the speech signal into smaller bandwidths. There are various ways of obtaining improved performance. The performance can be improved by the increasing the so-called 'talk power1 of the signals. This really means making the signal as effective and powerful as possible within given peak amplitude limits. Most voice links have some form of processing to boost performance even it is only in the form of some simple filtering.